O Teorema da Dominação de Pietsch Unificado - Moreira, Thiago Ginez Velanga (2010)
In this work we study a recent unified version of Pietsch Domination Theorem, due to Botelho, Pellegrino and Rueda ([8]) that unifies a number of known Pietsch-type domination theorems for classes of mappings that generalize the ideal of absolutely p- summing linear operators. A final result shows that Pietsch-type domination theorems are totally free from algebraic conditions, such as linearity, multilinearity, etc.